Case Writing on the Training Department of PM Malaysia - Lai, Kok Heng (1999)
The purpose of this case writing is to identify and highlight the problems faced by the training and development department of PM Malaysia, one of the leading audit firm incorporated in Malaysia. the problem identified are such as skill of the training department organizer, skill of the trainers, poor training environment, negative perception of the participants and limited resources of the training department. This case writing also suggests the potential solutions in relation to the problem encountered. Finally, the recommendations of the best solution have also been made based on the cost-benefit analysis.